Stars and stellar populations in Milky Way and the nearby galaxies - Sivarani T.; Subramanian S.; Bandyopadhyay A.; Banerjee P.; Bhattacharya S.; Choudhury S.; Ghosh S.; Hema B.P.; Jog C.; Hota A.; Joshi Y.; Karinkuzhi D.; Maitra C.; Malhan K.; Nayak P.K.; Pandey G.; Reddy E.; Sarkar S.; Sharma M.; Singh G.; Verma K.; Yerra B.K. (My University, 2025)
This article addresses key open questions in the Milky Way and neighboring galaxies, focusing on utilizing stars and stellar populations to trace galaxy formation and evolution processes. It offers an overview of the current landscape based on community-contributed white papers and outlines emerging research avenues alongside specific observational strategies relevant to the Indian context. Recent advancements in observations, such as precision astrometry from Gaia and asteroseismology enabled by Kepler, have reinvigorated interest in stellar physics, including its role in characterizing exoplanet atmospheres and understanding planet formation and evolution. Upcoming projects like the Rubin Observatory (LSST) and future large spectroscopic surveys will significantly enhance our ability to study stellar populations across various galaxies. These efforts will improve our understanding of dark matter distribution in galaxies, galaxy formation, and their evolution. Furthermore, by studying galaxies within the local volume, researchers can delve into the history of the formation of low-mass dwarf galaxies, the most common type of galaxy in the Universe. The local volume presents an excellent opportunity to test theories of hierarchical galaxy formation and assembly, especially since high-redshift observations of these galaxies’ formation epochs are beyond the reach of current telescopes. Therefore, this article seeks to summarize the current understanding and chart a path forward for the field. © Indian Academy of Sciences 2025.